Chrysoperla Mohave (Banks) Neuroptera: Chrysopidae: Two Familiar Species in an Unexpected Disguise - Charles S. Henry (Psyche: A Journal of Entomology)
The vibrational courtship song of Chrysoperla mohave (Banks) from several widely separated sites in California is described and compared to C. downesi (Smith) and to a C. mohave-like population of the recently described species. C. johnsoni Henry, Wells, and Pupedis. Unexpectedly, C. mohave is shown to have a song very much like that of C. downesi, in contrast to the very different song of mohave-like C. johnsoni. Yet the C. downesi and C. johnsoni versions of "C. mohave" are physically indistinguishable. Therefore, C. mohave is not a monophyletic taxon, but instead it is a color morph that has arisen independently at least twice in separate lineages of Chrysoperla. Both C. downesi and C. johnsoni are thus highly variable species, encompassing populations that range from solid dark green or bright green with no markings to light yellowish-green with tergal spottig and dark crossveins. It is argued that C. downesi should be taken from synonymy with C. carnea (Stephens) and recognized as a valid biological species or species complex, defined by a unique type of courtship song.